Dialog Antaragama Sebagai Strategi Membangun Kerukunan Umat Beragama Di Indonesia - Yosef Valdo Leso (Jurnal Ilmu Pendidikan Pancasila, Kewarganegaraan, dan Hukum, 2026)
This study examines interfaith dialogue as a solution to reduce religious conflict in Indonesia, a country characterized by its pluralistic reality. Religious conflict is not only triggered by theological differences but also by political interests, exclusive attitudes, claims of absolute truth, and the limited space for communication among religious communities. This research employs a qualitative method with a literature study approach by analyzing various relevant scientific sources. The findings indicate that interfaith dialogue is a strategic instrument in building harmony and social peace. The thought of Hans Küng emphasizes that world peace cannot be achieved without peace among religions, while Abdurrahman Wahid highlights the importance of dialogue rooted in humanistic values. This study proposes three forms of dialogue as an implementation model: dialogue of life, dialogue of values, and dialogue of education. These three forms of dialogue play a role in reducing prejudice, building ethical awareness, and shaping an inclusive society. Thus, interfaith dialogue becomes an essential foundation for realizing a harmonious, tolerant, and peaceful society.